The Distribution and Ecology of Medium to Large Mammals within an Oil Palm Plantation in Sarawak - Lok, Lisa Choy Hong (Universiti Malaysia Sarawak (UNIMAS), 2021)
Oil palm, while beneficial to the economy, is a prominent threat to biodiversity. Much of the oil palm expansion takes place in the tropics which is highly biodiverse and rich in endemism such as Borneo. While mammals play significant roles in regulating the ecosystem by facilitating seed dispersal, trophic regulation, and nutrient recycling, they are one of the most threatened taxonomic group as a result of agricultural expansion. There is relatively little information on the persistence of mammals in large scale oil palm plantations in Sarawak. Camera trap assessments of medium to large mammals was conducted in Wilmar-PPB Oil Palm Plantation in Miri, Sarawak from November 2018 to February 2020, and recorded a total 21 species from a total of 14,838 independent photos over 8,067 camera trap nights. Records of mammals largely followed a predicted pattern of decline away from the forest edge. Activity patterns of the target group showed no significant differences between the oil palm and forest fragments. Greater intactness of forests represented by the greater number of canopy trees were found to have a positive effect on three species, while none of the microhabitat variables in the oil palm had strong effects on mammalian occurrences. Occupancy of mammals were greater in the forest compared to the oil palm, except for the Leopard Cat and Common Palm Civet. Habitat type, distance to forest and distance to river were the top models that influenced selected species in this study. Leopard Cats and Pig-tailed Macaques recorded the greatest relative abundance in this study, highlighting their potential as biological pest regulators in oil palm plantations. Key conservation areas were also identified in the middle sections of Bukit Durang HCVF to allow management to focus resources strategically. In conclusion, this study highlights the importance of forest fragments within oil palm plantations and suggests that conservation efforts should have greater focus on landscape heterogeneity to improve biodiversity conservation. However, ecological enhancements such as restoration of degraded areas, improving forest edges, and buffer creations should also complement this effort, whenever possible.